2012
DOI: 10.1002/pbc.24193
|View full text |Cite
|
Sign up to set email alerts
|

CTC1 Mutations in a patient with dyskeratosis congenita

Abstract: Dyskeratosis congenita (DC) is a rare inherited bone marrow failure syndrome caused by mutations in 7 genes involved in telomere biology, with approximately 50% of cases remaining genetically uncharacterized. We report a patient with classic DC carrying a compound heterozygous mutation in the CTC1 (conserved telomere maintenance component 1) gene, which has recently implicated in the pleiotropic syndrome Coats plus. This report confirms a molecular link between DC and Coats plus and expands the genotype-phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 18 publications
1
100
0
2
Order By: Relevance
“…19 Two patients (F1: II-1 and F2: II-1) in this study lacked retinopathy, whereas F2: II-1 and F5: II-3 had no reported brain abnormalities. These observations show that although most patients with CTC1 mutations usually have retinal abnormalities and intracranial calcifications, there is a subset lacking either or both of these features (Table 1).…”
Section: Clinical Presentationmentioning
confidence: 93%
“…19 Two patients (F1: II-1 and F2: II-1) in this study lacked retinopathy, whereas F2: II-1 and F5: II-3 had no reported brain abnormalities. These observations show that although most patients with CTC1 mutations usually have retinal abnormalities and intracranial calcifications, there is a subset lacking either or both of these features (Table 1).…”
Section: Clinical Presentationmentioning
confidence: 93%
“…Consistent with this genome-wide role in replication, CTC1 and STN1 were originally identified as a pol ā£ accessory factor (AAF) that stimulates template binding and enzyme processivity (31,32). Recently mutations in CTC1 were found to underlie several diseases including dyskeratosis congenita and Coats plus (33)(34)(35). Additionally, single-nucleotide polymorphisms associated with human STN1 (OBFC1) correlate with the presence of short telomeres (36,37).…”
mentioning
confidence: 96%
“…Genetic variants of Stn1 are associated with increased telomere length in leukocytes [7] and expressing a deletion mutant of Stn1 in cancer cells causes telomere lengthening [5], suggesting that Stn1 may be involved in telomere length regulation. Recently, mutations in Ctc1 have been isolated from patients with telomere disorder dyskeratosis congenita (DC) and patients with Coats Plus (CP) syndrome, a complex genetic disease clinically related to DC [8][9][10]. Shortened telomeres were observed in both CP and DC patients carrying Ctc1 mutations [8,10], suggesting that the underlying cause for CP may be related to defective telomere maintenance induced by Ctc1 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mutations in Ctc1 have been isolated from patients with telomere disorder dyskeratosis congenita (DC) and patients with Coats Plus (CP) syndrome, a complex genetic disease clinically related to DC [8][9][10]. Shortened telomeres were observed in both CP and DC patients carrying Ctc1 mutations [8,10], suggesting that the underlying cause for CP may be related to defective telomere maintenance induced by Ctc1 mutations. Though it has been shown that transient depletion of Ctc1 or Stn1 in HeLa leads to telomere instability [3,4], the precise role of human CST complex is largely unknown.…”
Section: Introductionmentioning
confidence: 99%